The Effect of Work Motivation and Work Discipline on the Performance of Employees of the Operational Division at PT Sucofindo Kalibutuh Surabaya - Moch Ridho Illahi; Mei Retno Adiwaty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze two important aspects of employee performance in the operational division of PT Sucofindo Kalibutuh Surabaya branch, namely the influence of work motivation and work discipline on employee performance. The method used in this study is a quantitative method, with the SMARTPLS analysis tool, which allows the researcher to evaluate the relationship between the variables studied comprehensively. The population of this study consists of 75 employees, and the entire population is also used as a research sample through the saturated sampling method. The findings of this study reveal that work motivation and discipline significantly influence employee performance, suggesting that improvements in both factors can positively impact productivity and work effectiveness in the company. This result reinforces the importance of motivation and discipline for operational success at PT Sucofindo Kalibutuh Surabaya Branch.